Pelatihan Pembuatan Susu Kedelai Kepada Siswa Di Mts Sulthon Fattah - Ratih, Arista; Yulianti, Eni; Handayani, Pitri; Zuhri, Rozana; Marlina, Leni; Wulandari, Eko; Elita, Defa Fit (Journal Of Human And Education (JAHE), 2024)
Soy protein has the highest content of essential amino acids compared to other legumes. Although soy milk has high nutritional benefits, there is still a lack of understanding and skills among students related to how to make it. In this context, efforts are needed to provide students with an understanding and practical skills regarding the benefits of soy milk and how to make it independently. The purpose of the service activity is to provide training on the process of making soy milk in a simple and practical way. The service activities were carried out at Madrasah Tsanawiyah (MTs) Sulthon Fattah. These results and discussions provide a positive picture of the role of education in shaping healthy behaviors and lifestyles, and illustrate the potential of students as agents of change in their communities. Through the sustainability of this kind of initiative, it is hoped that positive changes in the health and diet of the community can be realized in the future.